Cold-induced changes in antioxidant defenses and reactive oxygen species in eight wild almond species - Sofo, Adriano; Rajabpoor, Shakiba; Yaghini, Hamid; Shirani, Maryam; Archangi, Azin; Ehsan Sangi, Seyed; Tavakoli, Farahnaz; Khodai, Mehdi; Sorkheh, Karim (Free Radicals and Antioxidants)
Introduction: Wild almond species (Prunus spp.) demonstrate a greater resistance to low temperatures due to their antioxidant defenses and so represent valuable germplasm sources for rootstock breeding. Methods: Eight genotypes of wild almond were subjected to two different cold treatments. The enzymatic and non-enzymatic antioxidant responses and the levels of some reactive oxygen species in leaves were measured. Results: The high ascorbate content and high ascorbate peroxidase activity found in some almond species contributed to the decrease in H2 O2 . Generally, catalase activity increased after the cold treatments, whereas superoxide dismutase activity and OH• levels varied markedly among the species. Conclusions: The differences in antioxidative traits among the almond species support the hypothesis of their importance in cold tolerance and could provide an useful probe to identify tolerant genotypes in breeding programs.
Keywords: α-tocopherol; Ascorbate; Antioxidant Enzymes; Cold Stress; Prunus Spp